THE PERSPECTIVES OF EFL STUDENTS ON THE TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) OF THEIR TEACHERS - Sahiruddin; Putri Ika Ayundha Ningtyas; Putu Dian Danayanti Degeng (Journey: Journal of English Language and Pedagogy, 2023)
The objective of this current research was examining EFL students' point of views on their teachers' TPACK (technological pedagogical content knowledge). A growing body of research had been conducted to investigate instructors' TPACK. However, few research have addressed the evaluation of TPACK from the perspective of EFL students. The students’ view offers a relatively objective perspective of instructors' TPACK to provide valuable feedback for further evaluation on their classroom practice. A survey method was employed by administered a TPACK student-based questionnaire adapted from Tseng (2014). The respondents were English education department students who had experience studying with technology, especially e-learning in the midst of pandemic. The findings showed that EFL students typically thought their teachers were knowledgeable about certain aspects of TPACK. Nevertheless, it was discovered that CK instructors were regarded as the greatest aspect of TPACK, whereas TK domain was thought to be the least important aspect. The results suggested that EFL teachers may need further TPACK training to attain the competency needed to properly incorporate technology more successfully in English lessons.